Study of stress relaxation in thermomechanical titanium nickelide-based junctions and methods for their reliability growth - V. A. Khokhlov; A. I. Potekaev; S. V. Galsanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The stress temporal changes were obtained due to the study of girth strength and energy dissipation in pipe thermomechanical junctions by nickelide titanium ferrule. The methods for their reliability growth were developed.